1995
DOI: 10.1063/1.469199
|View full text |Cite
|
Sign up to set email alerts
|

Structures, energetics, and spectra of aqua-sodium(I): Thermodynamic effects and nonadditive interactions

Abstract: Using extensive ab initio calculations including electron correlation, we have studied structures, thermodynamic quantities, and spectra of hydrated sodium ions [Na(H2O)+n (n=1–6)]. Various configurations were investigated to find the stable structures of the clusters. The vibrational frequency shifts depending on the number of water molecules were investigated along with the frequency characteristics depending on the presence/absence of outer-shell water molecules. The thermodynamic quantities of the stable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
79
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(92 citation statements)
references
References 42 publications
13
79
0
Order By: Relevance
“…And finally, one real limitation is that without previous knowledge of the CN, the system to consider cannot be accurately defined. For example, according to a lot of theoretical studies, 2 the most stable structure of Na(H 2 O) 6 ϩ clusters is a (4 ϩ 2) one (i.e., four molecules directly coordinated to the cation), whereas in dilute solution the CN of Na ϩ is known to be 6. Hence, we have to consider an isomer that has a higher energy and apply a PCM model if we hope to accurately reproduce the bulk properties by ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…And finally, one real limitation is that without previous knowledge of the CN, the system to consider cannot be accurately defined. For example, according to a lot of theoretical studies, 2 the most stable structure of Na(H 2 O) 6 ϩ clusters is a (4 ϩ 2) one (i.e., four molecules directly coordinated to the cation), whereas in dilute solution the CN of Na ϩ is known to be 6. Hence, we have to consider an isomer that has a higher energy and apply a PCM model if we hope to accurately reproduce the bulk properties by ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Lombardi and Jansen [3] also extended the approach to four-body interactions and found that these effects were negligible for most geometries of interest. These observations have been illustrated for a monatomic gas [4] and numerous cases of ions in aqueous solution [5][6][7][8]. In addition, recent studies of Na(I), Mg(II), or Zn(II) solvation in liquid ammonia by Monte Carlo simulations showed that the three-body corrections reduce their first shell coordination number from 9 to 8, 10 to 6, or 9 to 6, respectively [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of electron correlation (3)(4)(5)(6), at least at the MP2 level, is essential to describe the bonds in such systems, and normally the use of a large basis set is necessary to yield accurate binding energies. This makes the computational cost too expensive.…”
Section: Introductionmentioning
confidence: 99%